WIRAUSAHA MUDA MANDIRI: Learning, Sharing & Practice - Mr Wahyudi; Mr Mukrodi; Hadyati Harras; Endang Sugiarti (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
There are two ways to survive, first work and second entrepreneurship. Choosing to be an entrepreneur is not easy, many things to learn, including yourself. Starting from building a business spirit, having knowledge, studying the market, creating products, and management. In this dedication opportunity, a qualitative method was chosen. Where all parties are directly involved in learning and practice. Activities carried out for 3 days, covered by studying theory, practice, and providing motivation. Where participants are encouraged to awaken the spirit of entrepreneurship by looking at the reality of business and business knowledge. The results of the activities provide conclusions; 1) to increase entrepreneurial activities in the community, the first thing it takes is building a business spirit, with routine business practice. 2) the role of tertiary institutions is mentoring by educating entrepreneurship. and 3) tertiary institutions bridge the community to get business assistance to the government